Spatial Analysis of the Economic Valuation of Mangrove Carbon Stocks in Banda Aceh City - Anggi Pratiwi; Wira Dharma; Dalil Sutekad (Postgraduate, University of Mataram, 2025)
Climate change or global warming is caused by an increase in Earth's surface temperature due to the greenhouse effect, with carbon dioxide (CO₂) as the primary contributor. Rising CO₂ levels trigger atmospheric warming, sea level rise, agricultural disruptions, and more intense storms. Carbon absorption from the atmosphere can be achieved through mangrove forests, which serve as natural carbon sinks. However, mangrove deforestation leads to carbon release. This study aims to measure carbon stock and the economic value of mangroves along the coast of Banda Aceh City using NDVI analysis. The results indicate that the lowest carbon value is 2.49505 × 10⁻⁶ tons per hectare, demonstrating very limited carbon storage capacity in certain areas. The total economic value of carbon stocks in four mangrove areas is Rp 2,400,026,446. This study is expected to provide insights into global warming, support the role of mangroves as carbon sinks, and serve as a foundation for further research on climate change.